2017
DOI: 10.1016/j.molstruc.2017.05.137
|View full text |Cite
|
Sign up to set email alerts
|

A combined experimental and theoretical study of the supramolecular self-assembly of the natural benzopyran 2,2-dimethyl-3-hydroxy-6-acetyl-chromane and its isomeric benzofuran 10,11-dihydro-10-hydroxytremetone

Abstract: A combined experimental and theoretical study of the supramolecular self-assembly of the natural benzopyran 2,2-dimethyl-3-hydroxy-6acetyl-chromane and its isomeric benzofuran 10,11-dihydro-10hydroxytremetone

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The presence of compound 1 in a plant that biosynthesizes 2,2-dimethylchromenes is noteworthy, because an epoxy derivative has long been postulated as the reaction intermediate from the prenylated p -hydroxyacetophenone to cyclic dimethylchromenes or benzofurans. After prenylation of a suitable p -hydroxyacetophenone, the double bond of the prenyl residue is oxidized to an epoxide, which then undergoes an intramolecular cyclization via a nucleophilic attack of the phenol at C-4, leading to the corresponding chromene or benzofuran (Figure ). So far, this key intermediate has not been isolated, due to its suspected chemical instability . Thus, this is the first report of a potential epoxide intermediate, leading to any of the chromene constituents of A. grandiflora .…”
Section: Results and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The presence of compound 1 in a plant that biosynthesizes 2,2-dimethylchromenes is noteworthy, because an epoxy derivative has long been postulated as the reaction intermediate from the prenylated p -hydroxyacetophenone to cyclic dimethylchromenes or benzofurans. After prenylation of a suitable p -hydroxyacetophenone, the double bond of the prenyl residue is oxidized to an epoxide, which then undergoes an intramolecular cyclization via a nucleophilic attack of the phenol at C-4, leading to the corresponding chromene or benzofuran (Figure ). So far, this key intermediate has not been isolated, due to its suspected chemical instability . Thus, this is the first report of a potential epoxide intermediate, leading to any of the chromene constituents of A. grandiflora .…”
Section: Results and Discussionmentioning
confidence: 90%
“…27−29 So far, this key intermediate has not been isolated, due to its suspected chemical instability. 30 Thus, this is the first report of a potential epoxide intermediate, leading to any of the chromene constituents of A. grandif lora.…”
Section: T H Imentioning
confidence: 77%
“…The 1 H and 13 C NMR spectroscopic data of 1 indicated the presence of a 1,3,4-trisubstituted benzene ring, two methyls, two methylenes (including one oxygenated), one olefinic methine, and two nonprotonated (including one ketone and one olefinic) carbon atoms. Detailed analysis of the 1 H and 13 C NMR data (Table 1) revealed that 1 is a prenylated phenol derivative similar to 4-hydroxy-3-(3-methyl-2-butenyl)acetophenone (HMBA, 8 ), which is the main secondary metabolite of Senecio nutans (Asteraceae), a medicinal plant of northwestern Argentina [10,11]. However, the resonances for one methyl at δ H 2.58 and δ C 26.1 in the 1 H and 13 C NMR spectra of HMBA were not present in those of 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The structure was particularly relevant since it would provide evidence for the involvement of an epoxide intermediate in the biosynthesis of 2,2-dimethylchromenes or benzofurans from prenylated phydroxyacetophenones. 2 On the basis of DFT prediction of chemical shifts and Jcouplings, performed and analyzed following the DP4+ 3 and J-DP4 4 protocols, the absolute stereochemical configuration of the structure 1 was proposed as (1′S,2′R). The authors, however, made an important conceptual mistake when claiming to be able to distinguish between enantiomeric structures only on the basis of the reported shifts and couplings.…”
mentioning
confidence: 99%
“…On the basis of standard 1D and 2D NMR experiments, the authors proposed that 1 should be the 4-hydroxy-3-(1′-angeloyloxy-2′,3′-epoxy-3′-methyl)­butylacetophenone shown in Figure . The structure was particularly relevant since it would provide evidence for the involvement of an epoxide intermediate in the biosynthesis of 2,2-dimethylchromenes or benzofurans from prenylated p -hydroxyacetophenones …”
mentioning
confidence: 99%